2020
DOI: 10.1044/2020_jslhr-19-00061
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Processing Differences in Toddlers With Autism Spectrum Disorder

Abstract: Purpose Auditory processing measures have been used in an attempt to understand the relationship between neurological mechanisms and autism spectrum disorder (ASD) symptomatology in school-age children. The focus of the current study was to understand neural auditory processing in 2- to 3-year-olds with ASD. Method Auditory processing measures (click auditory brainstem responses and speech-evoked frequency-following responses) were hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…The most common ABR finding is that the wave is prolonged in ASD (Rosenhall et al, 2003;Tas et al, 2007;Azouz et al, 2014;Kamita et al, 2020). IPL of peak I-V differences are found as well (Figure 2B; Ververi et al, 2015;Jones et al, 2020).…”
Section: Functional Studiesmentioning
confidence: 65%
See 1 more Smart Citation
“…The most common ABR finding is that the wave is prolonged in ASD (Rosenhall et al, 2003;Tas et al, 2007;Azouz et al, 2014;Kamita et al, 2020). IPL of peak I-V differences are found as well (Figure 2B; Ververi et al, 2015;Jones et al, 2020).…”
Section: Functional Studiesmentioning
confidence: 65%
“…A study concluded that latencies of all speech-evoked ABR waves and V-A complex duration are longer in the ASD group compared to healthy controls (Ramezani et al, 2019). Other studies found differences in specific waves such as latencies in waves C, D, E, F (El Shennawy et al, 2014), and wave O (El Shennawy et al, 2014;Jones et al, 2020). Moreover, a difference in amplitude between the ASD and the control groups is observed in waves C, D, E, F, and O (El Shennawy et al, 2014).…”
Section: Functional Studiesmentioning
confidence: 98%
“…Moreover, interpeak intervals were longer in PA compared to control (Strata et al, 2005). Similar to the ABR alterations in autistic individuals (Tanguay et al, 1982;Maziade et al, 2000;Rosenhall et al, 2003;Tas et al, 2007;Russo et al, 2008;Magliaro et al, 2010;Azouz et al, 2014;Ververi et al, 2015;Jones et al, 2020;Kamita et al, 2020).…”
Section: Perinatal Anoxia (Pa)mentioning
confidence: 55%
“…As previously discussed, the morphology of SOC is found to be altered in the post-mortem brains of autistic individuals (Kulesza and Mangunay, 2008;Kulesza et al, 2011;Wegiel et al, 2014;Mansour and Kulesza, 2020). Moreover, abnormalities in peak III-V IPL (Figure 2B) are found (Rosenhall et al, 2003;Tas et al, 2007;Azouz et al, 2014;Jones et al, 2020;Kamita et al, 2020). The most common ABR finding is that the wave is prolonged in ASD (Rosenhall et al, 2003;Tas et al, 2007;Azouz et al, 2014;Kamita et al, 2020).…”
Section: Functional Studiesmentioning
confidence: 60%
See 1 more Smart Citation